Scientific issues relevant to setting regulatory criteria to identify endocrine-disrupting substances in the European Union - Slama, Rémy; Bourguignon, Jean-Pierre; Demeneix, Barbara; Ivell, Richard; Panzica, Giancarlo; Kortenkamp, Andreas; Zoeller, R. Thomas (National Institute of Environmental Health Sciences, 2016)
Background: Endocrine disruptors (EDs) are defined by the World Health Organization (WHO) as exogenous compounds or mixtures that alter function(s) of the endocrine system and consequently cause adverse effects in an intact organism, or its progeny, or (sub)populations. European regulations on pesticides, biocides, cosmetics, and industrial chemicals require the European Commission to establish scientific criteria to define EDs. Objectives: We address the scientific relevance of four options for the identification of EDs proposed by the European Commission. Discussion: Option 1, which does not define EDs and leads to using interim criteria unrelated to the WHO definition of EDs, is not relevant. Options 2 and 3 rely on the WHO definition of EDs, which is widely accepted by the scientific community, with option 3 introducing additional categories based on the strength of evidence (suspected EDs and endocrine-active substances). Option 4 adds potency to the WHO definition, as a decision criterion. We argue that potency is dependent on the adverse effect considered and is scientifically ambiguous, and note that potency is not used as a criterion to define other particularly hazardous substances such as carcinogens and reproductive toxicants. The use of potency requires a context that goes beyond hazard identification and corresponds to risk characterization, in which potency (or, more relevantly, the dose–response function) is combined with exposure levels. Conclusions: There is scientific agreement regarding the adequacy of the WHO definition of EDs. The potency concept is not relevant to the identification of particularly serious hazards such as EDs. As is common practice for carcinogens, mutagens, and reproductive toxicants, a multi-level classification of ED based on the WHO definition, and not considering potency, would be relevant (corresponding to option 3 proposed by the European Commission).